Analysis of Parents' Interpersonal Communication Patterns to Shape Children's Personalities in Siangkat Village, Dairi Regency - Annisa Dwi Utari Harahap; Muhammad Alfikri; Jufri Naldo (Pena Cendekia Insani, 2023)
This study is entitled Analysis of Interpersonal Communication Patterns of Parents and Children to Shape Children's Personalities in Sidiangkat Village, Dairi Regency. How interpersonal communication patterns of parents and children to shape children's personalities and how different communication patterns of parents to the eldest and youngest children. This study uses a descriptive qualitative approach that aims to understand a phenomenon experienced by the research subject, techniques used in data collection, observation methods, interview methods, and documentation methods. The theories used are analysis theory and social penetration theory. The results of the study can be concluded that parents adhere to the pattern of authorithative interpersonal communication, namely communication that refers to the climate of social relations in the family, the application of rules, parental recognition, giving rewards or punishments or can be called by responding to all children's actions. Communication differences between parents and children unconsciously inevitably occur. In accordance with ethical theory, a person will use different messages depending on the person's perception of the situation and the listener.